University research and the location of business R&D - Laura Abramovsky; Rupert Harrison; Helen Simpson (Institute for Fiscal Studies (IFS), 2006)
We investigate the relationship between the location of private sector R&D labs and university research departments in Great Britain. We combine establishment-level data on R&D activity with information on levels and changes in research quality from the Research Assessment Exercise. The strongest evidence for co-location is for pharmaceuticals R&D, which is disproportionately located near to relevant university research, particularly 5 or 5* rated chemistry departments. This relationship is stronger for foreign-owned labs, consistent with multinationals sourcing technology internationally. We also find some evidence for co-location with lower rated research departments in industries such as machinery and communications equipment. – Innovation ; Geography ; Spillovers ; Public Research
Keywords: O3; R11; R13; I23; 330; Hochschulforschung; Betriebliche Forschung; Standort; Betriebliche Standortwahl; Großbritannien